Road Rage - Rendell R. Ruth (London, Arrow, 1998)
A novel featuring Chief Inspector Wexford, whose wife allies herself to a protest movement when a by-pass is planned for Kingsmarkham, but the plot thickens when the lifeless body of a young woman is discovered, and people go missing, including his wife.